(untitled) (Al-Academy, 2024)
The post-modern period witnessed the emergence of advanced artistic methods due to many aesthetic and artistic variables, which formed the basis for the emergence of new and innovative concepts in the field of design that were affected by these variables, especially the emergence of the school of hyper-realism, which tends to dazzle the recipient with the ability to formulate an artistic work that conveys the smallest details. Similar to reality through a creative simulation that has its own unique features, and whose formal features and artistic trends began to spread in a hyper-realistic design mixture that inspires astonishment for those arts that gave the designer a new way of presenting ideas and a different vision for design, and in an era where machines have become the leaders in achieving what he is unable to achieve. Humans have the same level of accuracy. Artificial intelligence techniques have emerged with great effectiveness in the artistic and creative field, paying attention to the high quality of the design work and its precise details by finding many innovative alternatives. Artificial intelligence has saved a lot of time and effort thanks to its capabilities in selecting ideas with ease and high accuracy. During the adoption of artificial intelligence, which derives its components from the need of society, as it is considered a creative art that carries a purposeful artistic message in attracting the attention of the recipient. The second chapter included the theoretical framework in two sections.The first section: The origins and concept of hyperrealism, the intellectual creativity of hyperrealism, the aesthetic dimensions of hyperrealism, while the second section: It included the emergence of artificial intelligence, the artificial intelligence technology for hyperrealism, applications in hyperrealism, and the third chapter included the research procedures that The descriptive approach was adopted to analyze advertising posters for Walt Disney Company’s American films for the period (2014-2019), and the fourth chapter included results, conclusions, proposals, and recommendations